Application of Bypass Heater System for Prevention of Overcooling in Diesel Engines - Darmansyah Darmansyah; Anhar Khalid; Muhammad Kasim; Muhammad Azhar (Jurnal Syntax Admiration, 2023)
Industrial and agency activities are currently strongly influenced by electricity supply from PLN. When the PLN electricity goes out, the generator will immediately turn on and all loads previously electrified by PLN power will move to the generator. This displacement occurs quickly and not gradually. Diesel engines (engines) will receive high loads when conditions are still not hot. Diesel engines take longer to heat compared to gasoline engines. This condition is referred to as overcooling. This study uses a bypass heater system to accelerate the heating process and prevent overcooling. From experiments that have been conducted show that the use of a heater as 3000 W for generators with a size of 400 kVa can reduce the heating period by 17 minutes (54%). In addition, it can reduce fuel consumption by an average of 0.5 lt/h during the heating period